2017
DOI: 10.1039/c6nr07967a
|View full text |Cite
|
Sign up to set email alerts
|

True non-contact atomic force microscopy imaging of heterogeneous biological samples in liquids: topography and material contrast

Abstract: The present work analyses how the tip-sample interaction signals critically determine the operation of an Atomic Force Microscope (AFM) set-up immersed in liquid. On heterogeneous samples, the conservative tip-sample interaction may vary significantly from point to point - in particular from attractive to repulsive - rendering correct feedback very challenging. Lipid membranes prepared on a mica substrate are analyzed as reference samples which are locally heterogeneous (material contrast). The AFM set-up is o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 51 publications
0
12
0
Order By: Relevance
“…S1c & S1d). The substantial phase decrease 30 for the triangular areas indicated their chemical transformation. The optical bleaching and disappearance of Raman and photoluminescence peaks characteristic of WS2 (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…S1c & S1d). The substantial phase decrease 30 for the triangular areas indicated their chemical transformation. The optical bleaching and disappearance of Raman and photoluminescence peaks characteristic of WS2 (Fig.…”
Section: Resultsmentioning
confidence: 98%
“…Recently, studies have shown that dynamic AFM allows imaging in a non-contact regime where essentially no forces are applied on the sample. 195 Non-contact imaging eliminates the cellular deformation caused by the mechanical contact from the scanning AFM tip, and thus is a promising way to improve imaging resolution. AFM is capable of probing specific molecular interactions via single-molecule force recognition spectroscopy with the use of functionalized tips.…”
Section: Discussion and Perspectivementioning
confidence: 99%
“…Again, these requirements cannot be met by most samples or most AFM setups. However, the principle idea that local attractive forces F attr are specific for the local chemical composition and structure (as shown before by ncAFM [15,29] and NF-DAFM [30]) can also be utilized for force spectroscopy under ambient conditions.…”
Section: Introductionmentioning
confidence: 99%